Atypical Presentations of Collagenous Gastritis Mimicking Celiac Sprue. (13th February 2023) - Evans, Mark G.; Guccione, Jack P.; Crymes, Anthony; Li, Xiaodong; Johnson, Cary A.; Chandan, Vishal S.; Lu, Yuxin
Abstract : Collagenous gastritis has been reported as a rare cause of nausea, diarrhea, weight changes, and early satiety in female patients. Here, we describe two women aged 43 and 71 years who presented with similar symptoms. Gastric biopsies from both individuals showed thickened, irregular subepithelial collagen bands (>10  μ m). The pathogenesis of collagenous gastritis is poorly understood, but it may be the presenting symptom for many underlying autoimmune conditions. In particular, there is a well-established connection between collagenous disorders of the gastrointestinal tract and celiac sprue, Sjögren syndrome, and lymphocytic colitis; however, none of these conditions had been diagnosed in our patients. The older woman had incidentally discovered hypogammaglobinemia and IgA deficiency, whereas the younger woman suffered from fibromyalgia. Although a gluten-free diet and budesonide have been effective in some cases, there is no standardized therapy for collagenous gastritis. Our patients trialed diet modification and have required no additional medical interventions.